KAJIAN EFEKTIFITAS KEBIJAKAN PADA KASUS DESTRUCTIVE FISHING MENUJU PENGELOLAAN WILAYAH PESISIR BERBASIS MASYARAKAT PADA PULAU-PULAU KECIL (STUDI KASUS PADA PULAU KARANRANG KABUPATEN PANGKEP SULAWESI SELATAN) - Nurdin, Nurliah (Bumi Lestari; Vol 10 No 2 (2010), 2010)
This study of evaluation on policy effecitivity on the destructive fishing in small islands and coastal zone. Many government policy have not been successfully implemented due the lack of suprevision and monitoring. The destruction of coral reef has impact on economic income in the coastal zone citizen. Indonesia has lost its tremendous oceanic resources as the cause of destrucitice fishing through chemincal bombing on the sea to catch fishes. Its not only disaster for the longevility of the many kind of fishes but also coral reef which can only be recovered for hundred years. It is no longer a government roles to maintain the sustainability of these lives, but society and stakeholders should be involved as a team to increase the quality of the coastal zone society by improving their knowledge and skill for their fishing.
Keywords: destructive fishing, coastal zone, coral reef, small islands